Miniaturised Instrumentation for the Detection of Biosignatures in Ocean Worlds of the Solar System - Chela-Flores, Julian (Frontiers in Space Technologies, 2021)
This review of miniaturised instrumentation is motivated by the ongoing and forthcoming exploration of the confirmed, or candidate ocean worlds of the Solar System. It begins with a section on the evolution of instrumentation itself, ranging from the early efforts up to the current rich-heritage miniaturized mass spectrometers approved for missions to the Jovian system. The geochemistry of sulphur stable isotopes was introduced for life detection at the beginning of the present century. Miniaturized instruments allow the measurement of geochemical biosignatures with their underlying biogenic coding, which are more robust after death than cellular organic molecules. The role of known stable sulphur isotope fractionation by sulphate-reducing bacteria is discussed. Habitable ocean worlds are discussed, beginning with analogies from the first ocean world known in the Solar System that has always being available for scientific exploration, our own. Instrumentation can allow the search for biosignatures, not only on the icy Galilean moons, but also beyond. Observed sulphur fractionation on Earth suggests a testable "Sulphur Hypothesis", namely throughout the Solar System chemoautotrophy, past or present, has left, or are leaving biosignatures codified in sulphur fractionations. A preliminary feasible test is provided with a discussion of a previously formulated "Sulphur Dilemma": It was the Galileo mission that forced it upon us, when the Europan sulphur patches of non-ice surficial elements were discovered. Biogenic fractionations up to and beyond δ34S = −70‰ denote biogenic, rather than inorganic processes, which are measurable with the available high sensitivity miniaturised mass spectrometers. Finally, we comment on the long-term exploration of ocean worlds in the neighbourhood of the gas and ice giants.